Degree and non-degree secondary teacher education programmes in Malaysia - Noor, Jumaat Sin Hj. Moh. 1936- (1970)
The purpose of the study is to make a detailed analysis of the degree and non-degree secondary teacher education in Malaysiaknown as Diploma in Education and Certificate in Education, respectively. In these two levels of teacher education, the study made particular reference to recruitment, selection and admission procedures, curricula and student teaching. When viewed through the economic perspective, this study shows how the problem of teacher preparation and supply takes its significance.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Teachers, Training of -- Malaysia